Love is Not a Passport to Sweden - Halliki Voolma (United Nations, 2018)
This paper investigates how women’s right to live free from violence operates in the context of insecure immigration status. It is based on qualitative research addressing intimate partner violence against women with insecure immigration status in England and Sweden, analysed within a human rights theoretical framework. Empirical data were collected through in-depth, semi-structured interviews with 31 survivors from 14 different non–European Union countries and 57 professional stakeholders from local, national, and international organizations. The paper identifies a tension between human rights and immigration control that is present in theory, policy frameworks, and migrant women’s lived experiences. It contends that this tension has led to a proliferation of rights’ statuses for migrant women who are exposed to intimate partner violence. A solution is offered in the form of an expansionist model of human rights whereby presence in a territory is the basis for recognition as a rights-bearing subject.